Less Is Better. Avoiding Redundant Measurements in Studies on Wild Birds in Accordance to the Principles of the 3Rs - de Jong, Adriaan (Frontiers in Veterinary Science, 2019)
The principles of the 3Rs apply to animal use in research regardless where the research is conducted. In wildlife research, particularly research on wild birds, 3R implementation lags behind research using laboratory, farm or pet animals. Raised 3R awareness and more field-adapted techniques and protocols are expected to improve the situation. Unpredictable access to animals entices the wildlife researcher to make the most of each caught animal, leading to potential over-use and violation of the 3Rs. In this study I statistically screened an existing set of bean goose biometric data for the existence of redundant measurement data. The results show that the distinction between the fabalis and rossicus subspecies (the main aim of the measurements) could be made with high accuracy on the basis of two, instead of the original 17 measurements. If the redundant measurements were excluded from the protocol, the geese would experience 82% reduction of time and 78% of estimated suffering. This would improve the welfare of the geese, ease the workload of the catching team and improve the quality of the research, all in accordance to the Principles of the 3Rs. For use in other studies that collect measurement data from animals, a step by step scheme for the statistical analyses is made available in an attached R script.